2012
DOI: 10.5424/fs/2012212-02172
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating methyl jasmonate for induction of resistance to Fusarium oxysporum, F. circinatum and Ophiostoma novo-ulmi

Abstract: Damping off is probably the most common disease affecting seedlings in forest nurseries. In south-western Europe, the pitch canker and the Dutch elm disease cause relevant economic looses in forests, mostly in adult trees. The ability of the chemical plant elicitor methyl jasmonate (MeJA) to induce resistance in Pinus pinaster against Fusarium oxysporum and F. circinatum, and in Ulmus minor against Ophiostoma novo-ulmi was examined. In a first experiment, an aqueous solution of MeJA 5 mM was applied to P. pina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 39 publications
2
29
2
Order By: Relevance
“…Other environmental factors, such as the chemical environment (Martín et al 2008b(Martín et al , 2010aVivas et al 2012) or the action of less aggressive Ophiostoma strains inducing tree resistance (Hubbes and Jeng 1981;Jeng et al 1983) should not be discarded as factors involved in environmental resistance. A deeper study of the fungal microbiome and its spatial distribution over the tree architecture, including seeds, could help to identify candidate mutualistic endophytes in elms.…”
Section: Resultsmentioning
confidence: 98%
“…Other environmental factors, such as the chemical environment (Martín et al 2008b(Martín et al , 2010aVivas et al 2012) or the action of less aggressive Ophiostoma strains inducing tree resistance (Hubbes and Jeng 1981;Jeng et al 1983) should not be discarded as factors involved in environmental resistance. A deeper study of the fungal microbiome and its spatial distribution over the tree architecture, including seeds, could help to identify candidate mutualistic endophytes in elms.…”
Section: Resultsmentioning
confidence: 98%
“…From the experience of the Spanish elm breeding programme, the high level of polymorphism obtained with the microsatellites selected allows rigorous identification of each clone. 196 196 196 196 194 196 194 198 196 196 196 196 194 194 The Spanish programme aimed to directly control DED (Solla & Gil 2003, Martín et al 2010b, Vivas et al 2012) and gain a better understanding of tolerance through new techniques (Martín et al 2005(Martín et al , 2007(Martín et al , 2008a. One of its medium-term priorities is to increase the genetic diversity of tolerant native elms.…”
Section: Resultsmentioning
confidence: 99%
“…This invasive forest pathogen is native to North America but has been recorded in various countries outside its natural range [25] and has greatly impacted most Pinus plantations worldwide [26]. In Spain, it was first isolated in nurseries and forest plantations of P. radiata and P. pinaster [27] and is now apparently well established in the north, representing the main threat to Pinus in this area [28], [29]. It has recently been shown that genetic selection of P. pinaster genotypes less susceptible to the pathogen could be an adequate measure to reduce the impact of the disease [30].…”
Section: Introductionmentioning
confidence: 99%